A Cultural Review of Gender roles and Power Dynamics in Arabic Proverbs. - Suhad R. Sadeq (مجلة الباحث, 2025)
Abstract This review critically examines gender-specific roles and power dynamics embedded in Arabic proverbs, highlighting how these cultural artifacts reflect and reinforce societal ideologies. Through a review of prior studies conducted in various Arabic-speaking contexts—including Omani, Moroccan, Sudanese, Palestinian, Yamani, and Hijazi cultures—the study reveals recurring patterns of female subordination and male dominance. Using a feminist and critical discourse analysis (CDA) framework, the paper explores how linguistic devices such as metaphor, symbolism, and allusion are employed in Arabic proverbs to perpetuate gender stereotypes. While a few proverbs portray women positively, they often confine them to traditional roles such as mothers or caregivers, reinforcing patriarchal expectations. The analysis reveals objectification, denial of autonomy, and symbolic silencing of women through proverbial language. By identifying these patterns, the study underscores the role of proverbs in normalizing gender inequality and calls for a reassessment of their continued usage in modern discourse. This study aims to fill the gap in culturally specific analyses of gender representation in Arabic proverbial literature and highlights the need for discourse that promotes gender equity in Arab societies